TURKEY-UAE BILATERAL RELATIONS: INTERDEPENDENCY IN CAUSES OF CONFLICT RECONCILIATION - Shafira Ramadhanty; Muhamad Syauqillah (Indonesian Journal of Multidisciplinary Science, 2022)
The study tries to analyze the dynamics of bilateral relations between Turkey and the United Arab Emirates and how interdependence leads to reconciliation between the two countries. Although there had been tensions between Turkey and the UAE due to differences in ideology and interests in the region, trade relations between the two countries continued. Qualitative methods are used and are based on the theory of interdependence and the concept of reconciliation in analyzing this phenomenon. The results showed that the interdependence in bilateral relations led to the reconciliation of conflicts that occurred between the two countries. Each country is more focused on its economic priorities than on highlighting. Conclusion Bilateral relations between Turkey and the UAE are based on the interdependence between the two countries. It began with the highest official visit of Turkey and the UAE on August 8, 1948, at the invitation of President Kenan Evren. Turkey, as an adherent of an export-based economic model, makes the UAE one of the important markets in Turkey.